The Implementation of the Regional Spatial Planning Policy (RTRW) In North Minahasa Regency - Dondokambey, Richard J. H.; Tumbel, Goinpeace H.; Siwij, Devie S. R. (International Journal of Information Technology and Education, 2025)
This study aims to analyze the implementation of the Regional Spatial Planning Policy (RTRW) in North Minahasa Regency, specifically in the context of settlement zoning. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation involving relevant stakeholders. The results indicate that RTRW implementation in North Minahasa Regency has progressed, as evidenced by increased compliance with settlement zoning and greater efficiency in permitting processes. Supporting factors include the utilization of an integrated Geographic Information System (GIS) with OSS-RBA, government budgetary support, and inter-agency coordination. However, several obstacles still impede policy effectiveness, such as regulatory inconsistencies, limited digital infrastructure, community resistance to restrictions on customary rights (hak ulayat), and relatively high administrative costs. Active participation of both the community and technical agencies in monitoring, zoning education, and local deliberations has been a crucial indicator for strengthening policy implementation. This study recommends harmonizing regulations across agencies, enhancing human resource capacity, reinforcing technological infrastructure, and adopting a sustained participatory approach. These findings contribute to the development of public policy, particularly in the field of sustainable spatial planning and regional management.